A Dosing Algorithm for Erythropoietin Alpha in Older Adults with Heart Failure and a Preserved Ejection Fraction - Altincatal, Arman; MacArthur, Robert B.; Teruya, Sergio; Helmke, Stephen; Maurer, Mathew S. (Cardiovascular therapeutics, 2013)
SUMMARY Aims: Erythropoietin stimulating agents (ESAs) is an active area of clinical investigation in heart failure (HF) but can cause hypertension and higher hemoglobin concentrations (Hb) that have been associated with adverse outcomes. We evaluated a dosing algorithm and potential confounders’ effect on Hb and blood pressure (BP) in a clinical trial. Methods: In an ongoing randomized, placebo controlled, single blind clinical trial of ESA (epoetin alfa) in anemic patients with HF and a preserved ejection fraction (HFPEF), Hb was measured weekly as was BP, weight and concomitant medical therapy. A repeated measure mixed model evaluated determinants of weekly changes in Hb and BP. Results: Among 45 subjects (78 ± 11 years, 67% women, EF = 57 ± 9%) with a total of 780 repeated weekly Hb measures, Hb significantly increased over time in those assigned to ESA (β= 0.933, P < 0.0001), compared to placebo. Dose (β=−0.108, P < 0.0001), patient weight (β=−0.016, P= 0.0037), diuretic use (β=−0.124, P= 0.0389), and time (β= 0.003, P= 0.0331), were all significantly associated with Hb change. Increased diuretic dose and weight change were significantly inversely associated with changes in Hb. ESA administration and dose were not significant determinants of absolute BP or changes in BP from baseline. Discussion: In addition to ESA dose and duration of therapy, factors indicative of volume status including weight and diuretic use are determinants of hemoglobin levels in HF subjects. Conclusion: The currently employed dosing algorithm, which adjusts the administration of ESA based on the absolute hemoglobin and weekly change in hemoglobin increases Hb with relatively a low weekly dose of ESA without significant effects on BP.